Best Practices in Islamic Integrated Competency-Based English Instruction: Insights from a Thai School - Piyawason, Soontorn (The Indonesian Institute of Science and Technology Research, 2024)
This study explores best practices in Islamic integrated competency-based English instruction, drawing from educational approaches in a Thai school setting. The aim is to illustrate how integrating Islamic values with English language teaching can enhance both language proficiency and students’ moral development. The instructional design prioritizes answering fundamental pedagogical questions—why, what, how, and how to evaluate—while focusing on specific competencies across cognitive, psychomotor, and affective domains. Teachers are encouraged to cultivate competencies incrementally, from foundational sub-skills to more complex capabilities, fostering holistic language mastery and moral growth. The curriculum aligns English learning with Islamic principles, integrating content and etiquette in listening, speaking, reading, and writing. Classroom management and control techniques are used to maintain an engaging, respectful learning environment, with reinforcement through positive language and Islamic expressions. This approach aims to build well-rounded students, capable of using English for real-life communication while upholding Islamic ethics, fostering skills such as self-discipline, critical thinking, teamwork, and adaptability to technology.